Simulated thoughts in virtual reality for negotiation training enhance self-efficacy and knowledge. Issue 139 (July 2020) - Ding, Ding; Brinkman, Willem-Paul; Neerincx, Mark A.
Highlights: Using the training system with virtual cognitions enhanced negotiation knowledge. The training system also improved people's self-efficacy. The self-motivational statements in virtual cognitions further boosted self-efficacy. The effects obtained from using the training system remained after multiple weeks. Abstract: Negotiating serves as an essential skill in our daily life, however, it is quite challenging to negotiate well. Various negotiation training systems have been developed to solve this problem and improve people's performance in negotiation. Nevertheless, these systems mainly focus on skills practice and less on negotiation understanding or self-efficacy development. Aiming at improving both people's negotiation knowledge and self-efficacy, a virtual reality negotiation training system is proposed that exposes users to virtual cognitions during negotiating with virtual characters. The virtual cognitions, delivered as a personalised voice-over, provide users with a stream of thoughts that reflects on the negotiation progress and their performance, and also presents self-motivational statements. To study the effectiveness of the system and the self-motivational statements included in virtual cognitions, an empirical study with 48 participants was conducted. The study employed a between-subjects design with three groups: waitlist, training with self-motivational statements, and training without self-motivational statements. 24 waitlist participants were also randomly assigned to and completed the training following the waiting period. The results indicated that 1) the system significantly enhanced people's knowledge about negotiation and increased their self-efficacy, 2) the self-motivational statements included in virtual cognitions even further improved self-efficacy. Furthermore, these effects remained after multiple weeks.